Pathology of skeletal muscle - Carpenter, Stirling; Karpati, George (Oxford University Press, 2001)
This book has been described as the \"bible\" of muscle disease, from both a scientific and a clinical point of view. It is a detailed yet practical, up-to-date text of human muscle pathology that not only describes but extensively and beautifully illustrates human myopathology. It includes histochemistry, immunoytochemistry, resin histology, and electron microscopy.
Keywords: patologie; neurologie